Housekeeping Supervision and Operational Performance: Evidence from a Five-Star Hotel in Bali - Diego Gilang Armada; I Wayan Seniartha; I Made Sucipta Adnyana (HeadWay Research & Developemnt, 2025)
Housekeeping supervision plays a critical role in maintaining operational quality and ensuring consistent service standards in the hospitality industry. This study aims to examine the supervisory role of housekeeping supervisors in maintaining operational quality at Conrad Bali. A qualitative case study approach was employed, with data collected through semi-structured interviews, direct observations, and document analysis. The participants included the Executive Housekeeper, housekeeping supervisors, and room attendants selected through purposive sampling. Data were analyzed using thematic analysis following the interactive model of Miles, Huberman, and Saldaña. The findings reveal that housekeeping supervisors contribute significantly to operational quality through effective planning, staff coordination, quality inspections, employee coaching, and cross-departmental communication. These supervisory practices ensure compliance with hotel standards, improve employee performance, enhance operational efficiency, and support guest satisfaction. Despite challenges such as high occupancy and staffing constraints, adaptive leadership and effective communication enable supervisors to maintain service consistency. The study highlights the strategic role of housekeeping supervisors in achieving operational excellence and provides practical insights for hotel management to strengthen supervisory competencies and sustain high-quality hospitality services.